Qualidade do leite e da cama em sistema Compost BARN - Muxfeldt, Luana (2020)
The aim of this study was to evaluate the microbiological quality of the bed in the Compost Barn confinement system, milk quality is well as its composition, SCC (Somatic Cell Count) and SPC (Standard Plate Count). The study was performed from October 2017 to December 2018, at two-month intervals. For the bed, the sampling was characterized for surface, 10 and 15 cm deep and where determined the bacterial counts for total aerobic mesophilic microorganisms, Staphylococcus spp., Enterobacteria spp., Clostridium spp., Streptococcus spp., fungi and yeasts, as well as pH, bed humidity and temperature. In relation to milk, total aerobic mesophilic microorganisms, Staphylococcus spp., Enterobacteria spp., Clostridium spp., Streptococcus spp. were evaluated, as well as the physical composition, SCC and SPC. The room temperature inside the shed (max. 23.5°C and min. 13.2°C) was close to the temperature of the bed surface (max. 26.34°C and min. 16.32°C), being observed on the surface the lowest values in relation to the depths of 10 and 15 cm (max. 46.24°C and min. 24.15°C) and (52.22°C and 27.91°C), respectively. With the increase in temperature, there was a reduction in the count of some microorganisms such as Streptococcus spp. Enterobacteria spp., Staphylococcus spp. and yeasts, especially when the temperature was above 46 ° C. While the genus Clostridium spp. demonstrated high counts during all collections. The fungi of the genera Rhizopus, Penicillium, Bipolar and Fusarium were predominant in bed. However, only the last two collections at 10 and 15 cm deep reached the ideal temperature (45-55°C) for the inhibition of pathogenic microorganisms. Milk production showed a negative correlation of 43% for fat and 62% for protein, whereas for lactose there was a positive correlation of 33%. Lactose showed a negative correlation of 41% with SCC and 31% for SPC. The increase in the microbial load of the bed can result in contamination of the milk and consequently lead to a change in the composition, since the microbial load of the milk influenced the increase in the SCC and SPC of the milk. Regarding the bed, the temperature presented a negative correlation of 88% with humidity, 20% for total aerobic mesophilic, 87% for Streptococcus spp. and 68% for Enterobacteria spp. and a positive correlation of 73% for Staphylococcus spp. It could have been observed that the microbiological quality and the composition of milk can be related to the microbiota of the bed.